A mesoscopic analysis of cavities in two components silicone adhesive with cylindrical butt joint specimens. (September 2022) - Seewald, R.; Schnittcher, M.A.; Pauly, F.; Rath, S.; Schaaf, B.; Lamm, L.; Schiebahn, A.; Brepols, T.; Reese, S.; Feldmann, M.; Reisgen, U.
Abstract: In the construction industry, silicone adhesives were firstly used as sealant because of their elasticity and resistance towards environmental exposition. Nowadays, modern façades need to fulfil thermal efficiency, while keeping transparent design. Structural glazing façades satisfy these requirements due to silicone adhesives. However, because of the complex nonlinear material behaviour of silicone adhesives, only a conservative dimensioning with linear material law using high safety factors is proposed in the European guideline ETAG 002. This investigation aims to quantify cavities in cylindrical butt-bonded specimens on a mesoscopic scale in two-component silicone adhesive for layers at minimum ETAG 002 requirement (4 mm). As hydrostatic tensile stress accounts for cavities, the necking transversal to the load has been monitored with digital image processing during tensile tests. In the developed in-situ tensile aperture cavities have been quantified with an X-ray micro-computed tomography (Micro-CT) on a mesoscopic scale at defined strain. With scanning electron microscopy (SEM) footprints of cavities on the fracture surface can be observed. As main conclusion cavities have been visualised in-situ under tensile load and quantified to volumes ranging from 0.0055 mm³ to 0.194 mm³.